PREDIKSI ALOKASI PRODUKSI LNG LAPANGAN TANGGUH DAN SENORO UNTUK PEMENUHAN KEBUTUHAN LISTRIK DAN EKSPOR INDONESIA - Zhorif, Aufa
LNG supply chain management is an important part of the LNG gas industry. The LNG supply chain can be defined as a set of activities related to the LNG gas industry, which includes production, extraction, transportation, and regasification. This of course makes the transportation of LNG gas for the government and contractors an important thing. And the distribution of LNG gas will affect whether the LNG gas project benefits the government or does not provide profits to the government based on NPV. Determination of the allocation of LNG gas for the government and contractors is an important aspect in the LNG gas industry because the Indonesian state applies LNG gas priority to the government where LNG gas from the government itself aims for the welfare of the community. Determining the allocation of gas for the government has several challenges that need to be considered, the first is the need for contractors from which they benefit, one of which is through export needs, and what the government needs, in this research, is the need for gas for the electricity sector. Thus, optimization of gas allocation is needed so that the determination of gas allocation for the government does not only benefit the government but the contractors' needs are met. This study uses decline curve analysis to predict gas production in the future, PSC cooperation contracts (both gross split and cost recovery), ARIMA time series to determine predictions of gas demand for electricity in the future, and non-linear optimization for completion. . Solving this non-linear optimization using the SLSQP method which is one of the functions in python. Through the methodology described previously, the results of the optimization of this case provide the percentage value of LNG gas allocation for the government that still meets the specified requirements, gas needs for electricity, and export.